2019
DOI: 10.1002/jcp.28969
|View full text |Cite
|
Sign up to set email alerts
|

Mst1 deletion reduces hyperglycemia‐mediated vascular dysfunction via attenuating mitochondrial fission and modulating the JNK signaling pathway

Abstract: Diabetes is a leading cause of microvascular complications, such as nephropathy and retinopathy. Recent studies have proposed that hyperglycemia-induced endothelial cell dysfunction is modulated by mitochondrial stress. Therefore, our experiment was to detect the upstream mediator of mitochondrial stress in hyperglycemia-treated endothelial cells with a focus on macrophage-stimulating 1 (Mst1) and mitochondrial fission. Our data illuminated that hyperglycemia incubation reduced cell viability, as well as incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…Our results corroborate the findings of previous researchers who showed that mitochondrial dysfunction is a key player in obesity and hypertension [22]. e mitigation of mitochondrial fission by Mst1 knockout in hyperglycemia-mediated vascular damage was also reported [23] and corroborated our present work. Another researcher has also conveyed that the antidiabetic drug metformin exerts its therapeutic effect by inhibition of mitochondrial fission [24].…”
Section: Discussionsupporting
confidence: 93%
“…Our results corroborate the findings of previous researchers who showed that mitochondrial dysfunction is a key player in obesity and hypertension [22]. e mitigation of mitochondrial fission by Mst1 knockout in hyperglycemia-mediated vascular damage was also reported [23] and corroborated our present work. Another researcher has also conveyed that the antidiabetic drug metformin exerts its therapeutic effect by inhibition of mitochondrial fission [24].…”
Section: Discussionsupporting
confidence: 93%
“…The present study also found that Mst1 knockout significantly improved myocardial microvascular endothelial integrity in HP mice, suggesting a role for Mst1 in endothelial cell function, consistent with the findings of a previous study (39). One factor that contributes to HP is the apoptosis of microvascular endothelial cells, as this directly leads to microcirculation reduction and peripheral resistance increase, both of which result in elevated blood pressure (10,40).…”
Section: Discussionsupporting
confidence: 92%
“…The time of blood glucose reaching the standard and the time of insulin pump were shorter than those who received ordinary care intervention, the insulin dosage was less than those who received ordinary care intervention, and the incidence of hypoglycemia was lower than those who received ordinary care intervention. The above results suggest that intensive care for optimal management of hyperglycemia can effectively control the blood glucose level, 3 Computational and Mathematical Methods in Medicine [21][22][23]. When insulin was injected intravenously, physiological insulin secretion mode was simulated as much as possible, and timely adjustment of enteral nutrition was helpful to control blood glucose fluctuation, effectively reduce blood glucose variability, and maintain blood glucose stability [24][25][26].…”
Section: Discussionmentioning
confidence: 95%
“…The above results suggest that intensive care for optimal management of hyperglycemia can effectively control the blood glucose level, reduce insulin dosage, and decrease hypoglycemia in patients after cerebral hemorrhage. This is due to high blood sugar optimization management intensive nursing intervention through regular monitoring of blood sugar, timely upload data to neurology and nutrition doctors, and jointly develop reasonable blood sugar control objectives, intervention of individualized insulin therapy, and nutritional intervention [ 21 23 ]. When insulin was injected intravenously, physiological insulin secretion mode was simulated as much as possible, and timely adjustment of enteral nutrition was helpful to control blood glucose fluctuation, effectively reduce blood glucose variability, and maintain blood glucose stability [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%